Galleria mellonella as a Suitable Model of Bacterial Infection: Past, Present and Future - Ménard, Guillaume; Rouillon, Astrid; Cattoir, Vincent; Donnio, Pierre-Yves (Frontiers in Cellular and Infection Microbiology, 2021)
The increasing interest for Galleria mellonella larvae as an infection model is evidenced by the number of papers reporting its use, which increases exponentially since the early 2010s. This popularity was initially linked to limitation of conventional animal models due to financial, technical and ethical aspects. In comparison, alternative models (e.g. models using Caenorhabditis elegans, Drosophila melanogaster or G. mellonella) were cheap, simple to use and not limited by ethical regulation. Since then, similar results have been established with G. mellonella model comparatively to vertebrates, and it is more and more often used as a robust model per se, not only as an alternative to the murine model. This review attempts to summarize the current knowledge supporting the development of this model, both on immunological and microbiological aspects. For that, we focus on investigation of virulence and new therapies for the most important pathogenic bacteria. We also discuss points out directions for standardization, as well as recent advances and new perspectives for monitoring host-pathogen interactions.